Effect of temperature and nutrients on the growth and development of seedlings of an invasive plant - Skálová, Hana; Moravcová, Lenka; Dixon, Anthony F G; Kindlmann, P; Pyšek, Petr (AoB PLANTS, 2015)
Plant species distributions are determined by the response of populations to regional climates; however, little is known about how alien plants that arrive in central Europe from climatically warmer regions cope with the temperature conditions at the early stage of population development. Ambrosia artemisiifolia (common ragweed) is an invasive annual plant causing considerable health and economic problems in Europe. Although climate-based models predict that the whole of the Czech Republic is climatically suitable for this species, it is confined to the warmest regions. To determine the factors possibly responsible for its restricted occurrence, we investigated the effects of temperature and nutrient availability on its seedlings. The plants were cultivated at one of seven temperature regimes ranging from 10 to 34 °C, combined with three nutrient levels. The data on the rate of leaf development were used to calculate the lower developmental threshold (LDT, the temperature, in °C, below which development ceases), the sum of effective temperatures (SET, the amount of heat needed to complete a developmental stage measured in degree days above LDT) and width of the thermal window. The rate of development decreased with decrease in temperature and nutrient supply. Besides this, the decrease in the availability of nutrients resulted in decreased LDT, increased SET and wider thermal window. The dependence of LDT and SET on the availability of nutrients contradicts the concept that thermal constants do not vary. Our results highlight temperature as the main determinant of common ragweed's distribution and identify nutrient availability as a factor that results in the realized niche being smaller than the fundamental niche; both of these need to be taken into account when predicting the future spread of A. artemisiifolia.
Keywords: invasive species; nutrient limitation; non-indigenous plants; plant nutrition; thermal time; Ambrosia artemisiifolia; rate of development; common ragweed